Analisis Kebutuhan Tenaga Rekam Medis Berdasarkan Beban Kerja Dengan Metode WISN Di Bagian Filling RSU Mitra Sejati Medan - Yeyi Gusla Nengsih; Lisa Anggriani Tanjung (Akademi Perekam dan Informasi Kesehatan Imelda, 2023)
Analysis of the medical record workload is very necessary in improving health services in a hospital. This aims to determine which workloads need to be streamlined. In addition, with the analysis or measurement of workloads, scientific evidence-based decision making can be made. Seeing the large role of medical records in health services in hospitals, it is necessary what things are needed to improve the best quality in medical record installations. The purpose of this study was to determine the need for medical record personnel based on the workload in the filling section of Mitra Sejati General Hospital Medan. This type of research is descriptive with a cross sectional approach with a population of 4 medical record officers. The place where the research was conducted was at Mitra Sejati General Hospital Medan because the hospital had problems regarding work requirements in the filling section. The available working time is based on the number of effective working hours in the medical record section, which is 2200 hours/year, in 1 day working hours are 8 hours. The above regulation is based on the number of working hours of medical record officers at Mitra Sejati Hospital Medan, the number of outpatient visits is 6098 patients/year and for inpatients is 14789 patients/year while the standard time allowance for officers is 0.01 minutes. Based on the results of the calculation of the need for filling officers using the WISN method, the total human resource requirements in the outpatient filling unit were 2.89 or 3 officers while the outpatient filling unit officers at Mitra Sejati General Hospital Medan were 2 people. Meanwhile, the total human resource requirements for the inpatient filling unit are 3.11 or 3 officers, while the inpatient filling staff at Mitra Sejati General Hospital Medan are 2 people, so there is still a need for additional medical records officers specifically in the filling section.